2017
DOI: 10.1007/s00425-017-2767-8
|View full text |Cite
|
Sign up to set email alerts
|

T-protein is present in large excess over the other proteins of the glycine cleavage system in leaves of Arabidopsis

Abstract: T-protein is present in large excess over the other proteins of the glycine cleavage system in leaves of Arabidopsis and therefore, exerts little control over the photorespiratory pathway. T-protein is the aminomethyltransferase of the glycine cleavage multienzyme system (GCS), also known as the glycine decarboxylase complex, and essential for photorespiration and one-carbon metabolism. Here, we studied what effects varying levels of the GCS T-protein would have on GCS activity, the operation of the photorespi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 49 publications
4
25
1
Order By: Relevance
“…As shown in Figure 4A, wild-type and trxo1 plants grew similarly (unchanged rosette diameter and leaf number) and were invariant from each other with regard to chlorophyll a fluorescence. In agreement with previous findings (Timm et al, 2018), gldt1 showed reduced growth (reduction in the rosette diameter), yellowish leaves, and lowered quotient of the variable versus the maximal fluorescence of PSII (F v /F m ) under photorespiratory conditions. Interestingly, the reduction of growth and PSII efficiency observed in the gldt1 mutant was further enhanced in the TxGT line (Fig.…”
Section: Deletion Of Trxo1 In the Gldt1 Background Intensifies The Phsupporting
confidence: 93%
See 3 more Smart Citations
“…As shown in Figure 4A, wild-type and trxo1 plants grew similarly (unchanged rosette diameter and leaf number) and were invariant from each other with regard to chlorophyll a fluorescence. In agreement with previous findings (Timm et al, 2018), gldt1 showed reduced growth (reduction in the rosette diameter), yellowish leaves, and lowered quotient of the variable versus the maximal fluorescence of PSII (F v /F m ) under photorespiratory conditions. Interestingly, the reduction of growth and PSII efficiency observed in the gldt1 mutant was further enhanced in the TxGT line (Fig.…”
Section: Deletion Of Trxo1 In the Gldt1 Background Intensifies The Phsupporting
confidence: 93%
“…Rationally, CO 2 concentrations were varied to distinguish between conditions with suppressed [high CO 2 , high carbon (HC), 1500 mL L 21 CO 2 , 9 h illumination] and active photorespiration after transferring the plants into normal air (390 mL L 21 CO 2 , 9 h illumination). For comparison, we included the GDC T-protein knockdown mutant gldt1, which is characterized by a ;70% reduction in total GDC activity (gldt1-1; Timm et al, 2018).…”
Section: Metabolic Effects Of Trxo1 Deficiency On Gly Turnover and Cementioning
confidence: 99%
See 2 more Smart Citations
“…To achieve high expression levels, we used the CaMV 35S viral promoter which has been widely and successfully used in the past to drive high expression of the desired transgene and in the production of high yielding plants (Kohler et al ., ; Lefebvre et al ., ; Simkin et al ., ). Additionally, the ST‐LS1 promoter, previously used for the overexpression of GCS proteins in A. thaliana (Timm et al ., , , ), allowed us to achieve an intermediate level of overexpression in leaves. Somewhat unexpectedly however, the two sets of transgenic plants had contrasting growth phenotypes, and the transgenic plants with the larger increases in H‐protein had a severe slow growth phenotype.…”
Section: Discussionmentioning
confidence: 99%